(untitled) (Journal of Shaheed Suhrawardy Medical College, 2024)
Background: Constipation is one of the common complaints of children with long-term hazardous consequences. It is a frequent cause of hospital visit in both primary and specialized care which needs proper evaluation and management. Recently in few studies, impairment of growth status has been reported as a result of functional constipation. But the relation is not well evaluated, especially in the pediatric population of our country. Aim: To assess the growth status of Bangladeshi children in functional constipation. Methods: This analytical study was conducted at the department of Pediatric Gastroenterology and Nutrition, BSMMU, Dhaka. A total 150 children aged 2-18 years were enrolled in this study. Children were divided into two groups, 75 having functional constipation (FC) and 75 healthy children with no constipation. Samples were collected randomly from pediatric out-patient department of BSMMU with consent of parents and child’s approval. Diagnosis of functional constipation was made by Rome IV criteria. Children with any red flag sign, chronic disease and on treatment of constipation were excluded from the study. Growth status (weight, height & BMI) was evaluated by using growth charts. Data collected in semi-structured questionnaire and analyzed by SPSS 23.0. Results: We evaluated 75 constipated children with the mean age of 7.61±3.50 years and 75 healthy children with the mean age of 7.40±3.88 years. The mean weight of children with functional constipation was 22.8±10.01 kg, mean height 117.7 ±18.4 cm and BMI 15.6±2.3 kg/m2. The mean weight of children with no constipation was 28.6± 13.72 kg, mean height 124.49±23.3 cm and BMI 18.11±2.9 kg/m2,demonstrated significant difference between two sets. In functional constipation group, on weight for age and height for age chart, 28% and 24% children were below the 3rd centile respectively and 18.6% children had BMI below 5th centile. All these parameters (weight, height, BMI) were statistically significant in compare to children without constipation and p value is <.05. Presenting features of functional constipation were anorexia (64%), abdominal pain (73.3%), hard stool (84%), blood mixed hard stool (13.3%) and nausea (34%). Conclusion: Growth impairment occurs in children with functional constipation in comparison to children without constipation. Children aged 2 to 18 years with functional constipation may have decelerated weight, height and BMI growth. And this observation needs further large-scale multicenter study for ensuring optimal growth of children with constipation. J Shaheed Suhrawardy Med Coll 2023; 15(1): 73-77